A study on adiponectin, uric acid, and C-reactive protein in prediabetic and diabetic subjects - Rachna Sharma; Pallavi Anand; Shrawan Kumar (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Diabetes and prediabetes are always on the rise over the past decade, but little is known about the development of type 2 diabetes mellitus dysfunction in young adults. The study was conducted in prediabetic and diabetic patients in order to belong to an anti-inflammatory hormone adiponectin and pro-inflammatory marker uric acid (UA) in these patients and also to determine the role of these markers in future cardiovascular disease (CVD) risk. MATERIALS AND METHODS: This case-control study was conducted at Rama Medical College and Hospital, Kanpur. Out of 400 participants recruited, 140 subjects were control, 140 were prediabetics, and the remaining 120 were controlled. The detailed history of the patients regarding age, gender, height, weight, and family history regarding obesity and other chronic illnesses was taken. Patients with medical complications or diseases and conditions that may affect levels of inflammatory markers were excluded from the study. The data analysis was done using SPSS 16 and the results were presented as mean ± standard deviation where P < 0.05 has been considered as statistically significant. RESULTS: The adiponectin level was found significantly decreased and C-reactive protein and UA levels were increased in both study groups (prediabetes and diabetes) while comparison was done with control group. Similarly, basic parameters including waist/hip ratio, body mass index, glycated hemoglobin, and fasting blood glucose were increased. CONCLUSION: The study showed that prediabetes and diabetes are diseases of inflammatory origin with a high level of pro-inflammatory molecules. These medications are not only potent risk factors for prediabetes and diabetes but also mediate significant future CVD risk in these patients.